PENERAPAN INTERNET OF THINGS (IoT) PADA SISTEM MONITORING RUANG SERVER DI PT. MACROSENTRA NIAGA BOGA - Fachrun Nisa; Nurul Chafid (JURNAL SATYA INFORMATIKA, 2021)
In today's world of information technology, the server's very important role as a data service provider for client computers, the server room temperature needs to be monitored periodically so that if at any time a temperature deviation outside the tolerance limit can be immediately identified and acted upon so that there is no damage to the server. In this study a design of temperature and humidity monitoring system was made in the server room using a DHT 11 sensor where the sensor is connected to the Arduino Mega 2560 and NodeMCU ESP8266, the output is web, buzzer, SMS and fan. If the detected temperature is above 33 ° C the buzzer will light up which serves to signal to the operator if the temperature is above the normal limit, there will also be an SMS notification as a warning, then the fan will turn on automatically to stabilize the server room temperature, then through NodeMCU ESP8266 inputted to database, but if the temperature is below 33° C. then the data will be directly inputted to the database and then displayed on the web, where on the web there is a table that displays data every few seconds that can move in real time. With this system the room temperature will be better monitored so as to minimize the risk of damage to the device.